Case Report: Clinical Variation in Children With Thrombopoietin Receptor (C-MPL) Mutations. Issue 1 (January 2018) - Lo, Clara; Alvarez, Elysia; Ohgami, Robert S.; Jeng, Michael
Abstract : Congenital amegakaryocytic thrombocytopenia (CAMT, MIM# 604498) is a rare congenital bone marrow failure syndrome which presents early in life with abnormal bleeding because of thrombocytopenia. Classically, megakaryocytes are decreased to absent in the bone marrow. The development of aplastic anemia early in childhood has led to the recommendation for early stem cell transplantation. Quantitative or loss-of-function mutations in the myeloproliferative leukemia gene (c-mpl), whose gene product functions as the thrombopoietin receptor, have been identified as causative for CAMT. Approximately 100 cases of CAMT are published in the medical literature. We describe 2 cases of CAMT who demonstrate disparate clinical courses, thereby highlighting phenotypic differences and increasing awareness of this clinical entity.